The Impact of Clinical Factors, ALK Fusion Variants, and BIM Polymorphism on Crizotinib-Treated Advanced EML4–ALK Rearranged Non-small Cell Lung Cancer - Lin, Yen-Ting; Liu, Yi-Nan; Shih, Jin-Yuan (Frontiers in Oncology, 2019)
Patients’ clinical factors and genetics factors such as anaplastic lymphoma kinase (ALK) fusion variants and BIM (Bcl-2-like 11) polymorphism were reported to be associated with clinical outcome in crizotinib-treated advanced non-small cell lung cancer (NSCLC). However, the results were still controversial. We analyzed outcome of 54 patients with known ALK fusion variants who received crizotinib for advanced NSCLC. 30 of them had successful BIM polymorphism analysis and 6 (20%) had a BIM deletion. Multivariate Cox regression analysis found that previous anticancer therapy (adjusted hazard ratio [aHR] 1.35, 95% CI, 1.04 – 1.76 for each additional line of therapy, p = 0.025) and Eastern Cooperative Oncology Group (ECOG) performance status ≥ 2 (aHR 8.35, 95% CI, 1.52 – 45.94, p = 0.015) were independent factors for progression-free survival (PFS). Only ECOG performance status ≥ 2 (aHR 7.20, 95% CI, 1.27 – 40.79, p = 0.026) was an independent factor for overall survival (OS). Neither ALK fusion variants nor the presence of a BIM deletion was associated with crizotinib PFS or OS. After adjusted with clinical factors, different ALK variants and BIM polymorphism might not be independent factors for crizotinib PFS or OS in advanced NSCLC with ALK rearrangement.